Enhanced two-phase contention window MAC protocol for wireless sensor networks applications - Borges, Luís Miguel Moreira (2012)
Nowadays, the user of Wireless Sensor Networks (WSNs) is becoming more and more demanding in terms of choice and diversity of applications. As a consequence, as the diversity of applications continues to grow there is a need to identify and classify the set of detailed characterization parameters that facilitates to sketch up a taxonomy for WSN applications. The proposed taxonomy identi es the services offered by each application makes a tool available to better understand the services and requirements of each application, along with a holistic overview of the WSN proposed application taxonomy. The research also involved the actual development of WSN applications within different research projects, namely in the elds of healthcare (Smart Clothing), civil engineering structure monitoring (INSYSM) and precision agriculture. Different medium access control mechanisms employ different collision avoidance schemes to cope with packet collision and retransmission, trading-off complexity, energy inef ciency and control of packet overhead. In particular, this PhD thesis addresses the study the packet collision probability for a MAC protocol that employs a collision avoidance mechanism with two contention window and consequent proposal of a model for the collision probability. Simulation results validate the model for saturated traf c. For unsaturated traf c and with a small number of nodes, the accuracy of the model is limited by numerical rounding. It is shown that, by using our analytical model, we have been able to obtain performance metrics such as network throughput and average service time for the successful transmissions. In addition, the Enhanced Reliability Decision Algorithm in the physical layer has been proposed. The frame capture effect (FC) feature has been implemented in the IEEE 802.15.4 compliant physical layer of the MiXiM framework. The proposed decision algorithm utilizes the Signal to Noise-plus-Interference ratio (SNIR) and the size of the packet to guarantee the delivery with certain reliability to the MAC layer, of a packet received at the PHY layer. A gain of more than 10 % has been achieved in the delivery ratio. Promising results have also been obtained for the SCP-MAC protocol with the FC effect enabled, for different values of reliability. As one of the main contributions of this thesis, an innovative ef cient multi-channel MAC protocol, based on SCP-MAC, was proposed, the so-called Multi-Channel Scheduled Channel Polling (MC-SCP-MAC) protocol. The in uential range concept, denial channel list (which considers the degradation metric of each slot channel), extra resolution phase algorithm and frame capture effect have been explored to achieve the maximum performance in terms of delivery ratio and energy consumption. It has been shown MC-SCP-MAC outperforms SCP-MAC and MC-LMAC in denser scenarios, with improved throughput fairness. Considering the in uential range concept reduces the redundancy level in the network facilitating to reduce the energy consumption whilst decreasing the latency. The conclusions from this research reveal the importance of an appropriate design for the MAC protocol for the desired WSN application. Depending on the objective or mission of the WSN application, different protocols are required. Therefore, the overall performance of a WSN application certainly depends on the appropriate development and application of the appropriate communication protocols (e.g., MAC, network layer).